'A sense sublime': The Harmony of Hearing and Re-Hearing in Wordsworth's 'Tintern Abbey'. Issue 1 (April 2022) - Lo, Yimon
Abstract : In a close reading of 'Lines Written a Few Miles Above Tintern Abbey', my article examines the poem's musical quality that is central to our understanding of the theme of revisitation and memory. My article posits a significant coherence between readers' aural involvement with the poem's formal musicality and the poet-speaker's own hearing and re-hearing experience within the poem. Situating the performative nature of 'Tintern Abbey' in relation to the theory of musical meaning and emotion inaugurated by music psychologist and philosopher, Leonard B. Meyer, my article presents a novel perspective on how the associative process of Wordsworth's auditory memory shapes the poet's unique definition and representation of harmony. By reading the poet's associative auditory experience and the poem's musical expressiveness as manifestations of the constructive tension between Wordsworth's tragic consciousness and personal optimism, I argue that 'Tintern Abbey' does not create harmony by diminishing and dissipating dissonance, but by sounding and sustaining a range of possibilities and varieties.